1933
DOI: 10.1021/ja01330a023
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Electrolytic Solutions. III. The Dissociation Constant

Abstract: We have used the adiabatic twin calorimeter method to determine the specific heats of aqueous solutions of lithium and sodium hydroxides at 25°f rom 0.04 m tcTover 2 m. From these data we have calculated the apparent molal heat^capacity of the solutes. When plotted against \/m they both give straight lines over the whole range of concentration. Equations are included for the apparent and partial molal heat capacities of the solute and the relative partial molal heat capacity of the solvent. From these it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
2

Year Published

1960
1960
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(118 citation statements)
references
References 0 publications
3
113
0
2
Order By: Relevance
“…5 The data are reproduced Fig. 3, and the fitting distance is 0.66 nm, which is a realistic value for this distance, as the sum of radii is equal to 0.60-0.72 nm depending on the radius chosen.…”
Section: A Case Imentioning
confidence: 81%
“…5 The data are reproduced Fig. 3, and the fitting distance is 0.66 nm, which is a realistic value for this distance, as the sum of radii is equal to 0.60-0.72 nm depending on the radius chosen.…”
Section: A Case Imentioning
confidence: 81%
“…(1, 27) is negligible. As is true for the ion-pair QBr, discussed above, the dissociation constant of the ion-pair QHB in chloroform has not been measured but can be estimated to be about (1,19,20). Therefore, dissociation may or may not be significant at concentrations as high as M. However, a calibration curve of absorbance at 440 nm versus CQHBTo in chloroform was found to be linear with zero intercept over the range of concentrations of interest.…”
Section: ~A D S B T B ~~~( a ) -Imentioning
confidence: 94%
“…The ion-pair QBr is present at too low concentrations to dimerize in chloroform (1). Dissociation of QBr in chloroform has not been studied but, based on the behavior of similar compounds in solvents of various dielectric constants, its dissociation constant is expected to be about lop7 (19,20). Thus, in the concentration range studied the undissociated ion-air will red om in ate, but at the lower end of the range there could possibly be significant dissociation.…”
Section: Distribution Of Q B Rmentioning
confidence: 99%
“…For example, Fuoss and Kraus (15) observed that (i-amyl),Npicrate forms two liquid phases in benzene above a concentration of 0.1 M. Other examples are HFeC1, (16) and NH,FeCl, (17) in diethylether and similarly Ga2Cl, (17) and (Bu),NAlBu, (18) in benzene. In all of these cases the two phases occur only within a certain range referred to as the miscibility gap.…”
Section: Kineticsmentioning
confidence: 99%